WE8.7 Are Virtual Clinics for General Surgery Here to Stay? – A Single Centre Analysis. (9th August 2022) - Leigh, Charlotte; Deb, Rita; Sheth, Hemant; Raje, Durgesh; Pore, Naresh; Soggiu, Fiammetta
Abstract: Aim: Virtual clinics were rapidly established during the COVID-19 pandemic to maintain outpatient surgical care. To evaluate their use, we analysed telephone clinic outcomes and their compliance with the NHS Referral to Treatment (RTT) guidelines. Method: Data was collected for patients booked into Upper GI Surgery clinics between September – December 2020 (n = 622). This included details of referral, appointments (first to most recent), patient attendance, and clinic outcomes (active monitoring, offered surgery, discharge, other). We compared first appointment management decisions between telephone and face-to-face clinics. Results: 317 patients had their first appointment via telephone; 179 patients were seen initially face-to-face. For first appointments, non-attendance rate was 9.8% (31/317) in telephone clinics versus 3.9% (7/181) in face-to-face clinics. At first appointment, 8.5% (27/317) of patients consulted via telephone were offered surgery compared to 20.1% (36/179) seen face-to-face. 22.4% (71/317) of telephone clinic patients were started on active monitoring at first appointment, compared to 31.3% (56/179) of patients assessed face-to-face. 31.3% (155/496) of all patients analysed were compliant with RTT guidelines – 57.4% initiated on active monitoring; 11.6% underwent surgery. Conclusion: Patients are less likely to be listed for surgery after their first assessment if this was via telephone appointment compared to face-to-face. Delays in physical examination, and clinician and/or patient hesitancy may contribute to this; higher non-attendance rates would further postpone outcomes. However, telemedicine does allow effective active monitoring. To better evaluate telemedicine's efficacy in sustaining timely patient care, comparison of compliance with the RTT guidelines for cases managed solely face-to-face pre-COVID-19 is warranted.